Modelling the storage modulus, transition temperatures and time–temperature superposition characteristics of epoxies and their composites - Cormier, Laurent; Joncas, Simon (Journal of thermal analysis and calorimetry, 2018)
Epoxies are widely used as adhesives and matrix material for composites in civil infrastructure. As such structures are likely to be exposed to a wide variety of environmental conditions over long service lives, knowledge of their time–temperature sensitivity is desirable. The present study proposes a model describing the evolution of storage modulus for epoxies and their composites subject to forced dynamic excitations over wide temperature and frequency ranges. The model is tested against results for one rubber toughened epoxy and one carbon–epoxy composite. Results show a good agreement between the model and experiments, both in terms of temperature and frequency effects. Moreover, the model is shown to provide an unambiguous definition of the frequency dependent glass transition temperature, which is found to naturally follow the expected Arrhenius relationship with regards to frequency. Activation energies for the glass transition temperature evaluated by the new approach are in good agreement with results from the literature. It is also shown that when accounting for the effect of frequency on the glass transition, the evolution of the time–temperature shift factor is continuous across the glass transition.